Pengaruh Customer Relationship Marketing dan Customer Value terhadap Loyalitas Nasabah Bank Sumut Medan - Harahap, Fatimah A. Rizki; Lestari, Indawati (Economics, Business and Management Science Journal, 2025)
This study aims to analyze the influence of Customer Relationship Marketing (CRM) and Customer Value on customer loyalty at Bank Sumut Medan. This study used primary data obtained from questionnaire answers distributed to 99 customer respondents. The research sample was selected by purposive sampling technique, while the number of samples was determined using the Slovin method. Data collection was carried out through physical questionnaires and Google Forms which were distributed to customers of PT. Bank of North Sumatra Medan Head Office. This study uses the multiple linear regression analysis method to test the relationship between variables. The results of the partial test show that Customer Relationship Marketing has a positive and significant effect on customer loyalty. Similarly, Customer Value has proven to positively and significantly influence customer loyalty. In addition, the results of simultaneous tests show that Customer Relationship Marketing and Customer Value together have a positive and significant effect on customer loyalty. The implications of this study confirm that an effective CRM strategy and increased Customer Value can increase customer loyalty. Therefore, Bank Sumut is advised to strengthen customer relationships through loyalty programs, more personalized services, and increased service value so that customers remain loyal to banking services.